2021
DOI: 10.3390/agriculture11040333
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal Inoculation Improves Mineral Content of Organic Potatoes Grown under Calcareous Soil

Abstract: Soil mycorrhization can play an important role for the qualitative improvement of organically grown “early” potato tubers especially in low fertility soils (such as calcareous ones), by ameliorating plant uptake of limiting mineral nutrients in the soil. Hence, the objective of the present research was to elucidate the impact of soil mycorrhization on the tuber minerals content of three potato cultivars organically grown in two locations with different soil characteristics. Our data revealed the keyrole of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…These data were in disagreement with a similar study conducted by Ruta et al [30], which did not find statistical differences among applied propagation methods. This discrepancy could be explained through the different genotypes and environments applied in the study, since the specificity of AMF-host plant relationship could have influenced the responses [44]. In the other hand, the present study has also shown that the 'propagation method × genotype' interaction was significant for seven out of the thirteen considered traits, including DHF and DHP.…”
Section: Discussionmentioning
confidence: 53%
“…These data were in disagreement with a similar study conducted by Ruta et al [30], which did not find statistical differences among applied propagation methods. This discrepancy could be explained through the different genotypes and environments applied in the study, since the specificity of AMF-host plant relationship could have influenced the responses [44]. In the other hand, the present study has also shown that the 'propagation method × genotype' interaction was significant for seven out of the thirteen considered traits, including DHF and DHP.…”
Section: Discussionmentioning
confidence: 53%
“…Notably, all treatments that indicated the highest plant fresh and dry weights did not always exhibit the highest content of chlorophyll and P concentration. Functional contributions to other plant nutrition by mycorrhizal resulted in the high plant growth, and these potential contributions were not covered in the plant growth variables in this study; for example, the influences of AM in increasing the uptake of other nutrients, such as N (Zhu et al, 2016), Ca and Zn (Salgado et al, 2016), andMg (Zare-Maivan et al, 2017), as well as Mn, Cu, and Zn (Lombardo et al, 2021), and some other benefits of AM.…”
Section: Discussionmentioning
confidence: 91%
“…Glomus mosseae ) (Douds et al, 2007 ; Lone et al, 2015 ; Chifetete and Dames, 2020 ; Deja-Sikora et al, 2020 ). The application of AMF-based inocula in pot, greenhouse, and field experiments confirmed that arbuscular mycorrhiza can increase potato tuber biomass (Davies et al, 2005 ; Hijri, 2016 ; Lombardo et al, 2021 ) and enhance potato resistance to many different phytopathogens, e.g., Rhizoctonia solani (Yao et al, 2002 ) and Phytophthora infestans (Gallou et al, 2011 ). However, the nature of the interaction between AM and potato viruses, the prominent pathogens of potatoes, is not well characterized (Deja-Sikora et al, 2019 ).…”
Section: Introductionmentioning
confidence: 93%